A study of requirements engineering practices among software developers at UUM Information Technology (UUMIT) - Lafta, Inam Abdullah (2015)
Requirements Engineering (RE) is a systemic and integrated process of eliciting, elaborating, negotiating, validating and managing the requirements of a system in software development project. UUM has been supported by various systems in academic, administrative, students’ affair and many others. Most of the current systems are developed and maintained by the Information Technology Department (UUMIT). The aim of this study is to review the current requirements engineering practices and proposing requirements engineering practices during software development at UUMIT. The outsourcing of software development is rapidly growing because of its allied benefits in the limited resources of the organizations. The main problem that is discussed in this research is the lack of studies that support software development activities at the Information Technology department (UUMIT). The study used quantitative methodology and systematic literature review to answer research questions. The main significance of this study is helping educational institutes to produce quality software development and saving cost and time by implementing requirements engineering practices. In addition to that, the study contributes to UUM by identifying the activity needed for software development so that the management is able to allocate budget to provide adequate and precise training as well as seminars for the software developers. The researcher investigated three variables; Requirements Description, Requirements Development (Requirements Elicitation, Requirements Analysis and Negotiation, Requirements Validation), and Requirement Management. The results from the survey showed that the current practice of requirement engineering in IT department of UUM is encouraging, but need for further development because most of RE practices associated with requirement development and requirement management are achieved on a regular basis and not frequently. The researcher recommended providing effective training programs for UUMIT staffs on RE practices and increases their understanding on system requirements using RE practices to develop better systems for the university. Further investigation is required in the future to understand the effect of other RE practices on software development